2012
DOI: 10.1002/jctb.3864
|View full text |Cite
|
Sign up to set email alerts
|

High absorption of endocrine disruptors by Hytrel: towards the development of a two‐phase partitioning bioreactor

Abstract: BACKGROUND Endocrine disruptors (EDs) contribute to the endocrine disrupting potential of urban wastewater because most wastewater treatment plants only partially remove these compounds. Many EDs are present at very low concentrations in wastewater, which explains why most wastewater treatment plants can only partially remove them. The development of a two‐phase partitioning bioreactor (TPPB) could represent an alternative for the extraction of these compounds from water prior to their biodegradation. This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…This sequestering phase reduces the aqueous substrate concentration to sub‐cytotoxic levels, and progressively re‐releases it to the cell‐containing aqueous phase in order to respond to the microbial metabolic demand. This dynamic process is regulated by thermodynamic equilibrium (the relative affinity of the substrate between the aqueous and sequestering phases) and cell metabolism …”
Section: Introductionmentioning
confidence: 99%
“…This sequestering phase reduces the aqueous substrate concentration to sub‐cytotoxic levels, and progressively re‐releases it to the cell‐containing aqueous phase in order to respond to the microbial metabolic demand. This dynamic process is regulated by thermodynamic equilibrium (the relative affinity of the substrate between the aqueous and sequestering phases) and cell metabolism …”
Section: Introductionmentioning
confidence: 99%
“…In a previous study (29), we demonstrated the potential of using Hytrel in a TPP system to extract and concentrate E1, E2, E3, EE2, BPA, and NP from water but also from treated wastewater that was spiked with these EDs. Hytrel 8206 is a copolymer of poly(butylene teraphthalate) and butylene ether glycol teraphthalate and is becoming one of the most used solid polymers in TPPBs for the degradation of pollutants and also for the transformation of molecules of interest (16, 18-21, 28, 38, 39, 54, 55).…”
Section: Discussionmentioning
confidence: 99%
“…The ED concentrations were determined using gas chromatography-mass spectrometry (GC-MS) as previously described (29). Briefly, the EDs extracted from Hytrel were first derivatized using silylation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations